Community science as a potential tool to monitor animal demography and human-animal interactions - Laëtitia Maréchal; Raul Lobo; Fintan McAdam; Elizabeth Simpson; Josephine Woolston; Mae Stanley; Teresa Romero; Jenny C. Dunn (Scientific Reports)
Abstract Community science can provide crucial insights into population dynamics and demography. To date, its effectiveness for understanding human-wildlife interactions has not been tested. This is vital for designing effective wildlife management plans. We used a case study of an individually marked population of mute swans Cygnus olor, to test the reliability of community scientist data for quantifying self-reported interactions. We compared 5,251 community scientist sightings of individually marked birds with 317 observations recorded through systematic recording methods, to test the reliability of sightings, and of self-reported human-swan interactions. 98.86% of ring readings were correctly reported; sighting reliability increased with experience and was higher when the observer fed the birds. Community scientist observations were reliable for quantifying family group size, but not clutch size. Self-reported data for assessing feeding interactions with wildlife were not comparable with systematic recording methods. 22% of standardised observations recorded supplementary feeding of swans by people. This is the first systematic quantification of the frequency of interaction of wild waterfowl with humans through supplementary feeding in the Northern hemisphere; we highlight potential impacts of this common human-wildlife interaction for both birds and people. We provide new insights into using community science methods as potential alternatives to more time-consuming systematic methods. Community science methods may be useful across a range of systems where humans and wildlife interact, but we highlight the need for validation of the reliability of community scientist data, particularly self-reported behaviours, before being used to inform management and conservation practices.